Penggunaan Teknologi Penginderaan Jauh Satelit dan SIG untuk Menentukan Luas Hutan Kota - R Assyfa El Lestari; I Nengah Surati Jaya (Institut Pertanian Bogor (IPB University), 2005)
This paper describes the use of satellite Remote Sensing Technology as well as Geographic Information System on determining the minimum coverage of urban forest. The study used the Oxygen demand approach of human, lifestock, industry as well as transpartotion vehicles for estimating the need of forest coverage. The existing urban forest coverage were derived from IKONOS and SPOT Satellite Imageries.The study found that the increase of the need for urban forest was dominantly affected by the significant increase of transportation verticles during the last 5 years. If the rates of the increase of population, lifestock as well as transportation vehicles does not change, the urban forest in Bogor city is only adequate up to the year 2015. This study recomends that an action should be made to anticipate the scarceness of clean air in Bogor City. The study also found that the central Bogor District has the lowest extent of urban forest.Key word: